2007
DOI: 10.1124/dmd.107.015222
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Methods for Estimating Unbound Drug Concentrations in the Brain Interstitial and Intracellular Fluids

Abstract: ABSTRACT:Concentrations of unbound drug in the interstitial fluid of the brain are not rapidly measured in vivo. Therefore, measurement of total drug levels, i.e., the amount of drug per gram of brain, has been a common but unheplful practice in drug discovery programs relating to central drug effects. This study was designed to evaluate in vitro techniques for faster estimation of unbound drug concentrations. The parameter that relates the total drug level and the unbound interstitial fluid concentration is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
194
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(199 citation statements)
references
References 37 publications
(33 reference statements)
4
194
1
Order By: Relevance
“…A potential caveat in using brain tissue homogenate to estimate f u,brain is that homogenization may change binding properties by unmasking binding sites that are not accessible to a drug in vivo. These concerns may be addressed by using a brain slice approach in which the brain structure remains intact Fridén et al, 2007).…”
Section: How To Use K P To Assess Brain Penetration?mentioning
confidence: 99%
“…A potential caveat in using brain tissue homogenate to estimate f u,brain is that homogenization may change binding properties by unmasking binding sites that are not accessible to a drug in vivo. These concerns may be addressed by using a brain slice approach in which the brain structure remains intact Fridén et al, 2007).…”
Section: How To Use K P To Assess Brain Penetration?mentioning
confidence: 99%
“…Therefore, alternative methods for estimating C u,brainISF have been developed; these methods combine measuring the amount of drugs in the whole brain, excluding the vascular spaces, (A brain ) with in vitro estimates of the unbound brain volume of distribution (V u,brain ). C u,brainISF is obtained by dividing A brain (mmol/g brain) by V u,brain (mL/g brain) for the drug (Fridén et al, 2009(Fridén et al, , 2007. Similarly, the unbound drug concentration in the plasma is obtained by multiplying the measured total plasma concentration by the estimated unbound fraction in the plasma (f u,p ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the design of drugs restricted to peripheral tissues is an issue for medicinal chemistry, drug efflux at the BBB also needs to be studied in vivo using reliable models . This is generally done in rats by estimating the steady-state unbound brain-to-plasma concentration ratio K p,uu,brain (C u,brainISF /C u,p ) (Fridén et al, 2009(Fridén et al, , 2007Gupta et al, 2006). The K p,uu,brain parameter describes the difference between the concentration of pharmacologically active unbound drug in the brain interstitial fluid (C u,brainISF ) and that in the plasma (C u,p ).…”
Section: Introductionmentioning
confidence: 99%
“…Several indirect validation studies have been published, such as comparing the projected brain to plasma concentration ratios with the observed ratios, or comparing the unbound brain fraction determined by brain homogenate method with that determined by brain slice method, or by CSF method (Kalvass and Maurer, 2002;Maurer et al, 2005;Becker and Liu, 2006;Liu et al, 2006;Summerfield et al, 2006Summerfield et al, , 2008. Recently, Fridén et al (2007) showed that C ub predicted C m within 3-fold of error for 10 of 15 compounds. In that study, the microdialysis for 14 of the 15 compounds was compiled from the literature, and all the data were generated using different methods or in different species.…”
mentioning
confidence: 99%